2012
DOI: 10.1161/circoutcomes.112.966168
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 Fatty Acids and Cardiovascular Outcomes

Abstract: Background— Early trials evaluating the effect of omega 3 fatty acids (ω-3 FA) reported benefits for mortality and cardiovascular events but recent larger studies trials have variable findings. We assessed the effects of ω-3 FA on cardiovascular and other important clinical outcomes. Methods and Results— We searched MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials for all randomized studies using dietary supplements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 37 publications
2
104
0
3
Order By: Relevance
“…Despite the positive findings with omega-3 fatty acid interventions in at-risk patient groups, supported by meta-analyses and biologically plausible candidate mechanisms, a series of studies published since 2010 have failed to replicate the earlier findings (20)(21)(22)(23)(24) and this has influenced the most recent meta-analyses which have concluded that there is little protective effect of supplemental omega-3 fatty acids on cardiovascular mortality, usually studied in atrisk groups of patients (12, [25][26][27]. It is important to recognize that the most recent studies of omega-3 fatty acids and cardiovascular mortality in at-risk patients have been criticized for various reasons related to small sample size, the low dose of EPA plus DHA used, and the too short duration of follow up (e.g., 28).…”
Section: Omega-3 Fatty Acids and Cardiovascular Disease: What Was Alrmentioning
confidence: 99%
“…Despite the positive findings with omega-3 fatty acid interventions in at-risk patient groups, supported by meta-analyses and biologically plausible candidate mechanisms, a series of studies published since 2010 have failed to replicate the earlier findings (20)(21)(22)(23)(24) and this has influenced the most recent meta-analyses which have concluded that there is little protective effect of supplemental omega-3 fatty acids on cardiovascular mortality, usually studied in atrisk groups of patients (12, [25][26][27]. It is important to recognize that the most recent studies of omega-3 fatty acids and cardiovascular mortality in at-risk patients have been criticized for various reasons related to small sample size, the low dose of EPA plus DHA used, and the too short duration of follow up (e.g., 28).…”
Section: Omega-3 Fatty Acids and Cardiovascular Disease: What Was Alrmentioning
confidence: 99%
“…However, the magnitude of the positive effects was not as great as was suggested by the older studies [24]. [25].…”
Section: Negative Meta-analysesmentioning
confidence: 52%
“…7 Amongst the thirteen trials reporting on cardiovascular mortality, there was a significant 14% reduction in risk overall, noting significant trial heterogeneity (I triglyceride levels (greater benefits with higher baseline triglyceride levels); age of trial participants (greater benefits in younger patients); and the presence of hypertension or diabetes (greater benefits in patients without these comorbidities). 7 Several trials in this meta-analysis had control groups which were on a Mediterranean diet, used olive oil as a control or had a fish rich diet, all of which could have masked the benefits of omega-3 supplementation with their own cardio-protective effects. A linear response to fish oil intake and CVD protection has never been established, suggesting supplementation beyond a certain level of intake may not confer additional benefits.…”
Section: Fish Oilsmentioning
confidence: 99%
“…No effect on cancer incidence has been reported in meta-analyses of eight randomised studies from a systematic review. 7 Currently the evidence base for the use of fish oils to reduce cardiovascular or mortality endpoints is limited, and general conclusions are that the available evidence is not adequate to strongly support the use or cessation of omega-3 fatty acids in the secondary prevention of CVD. 7 Australian secondary prevention guidelines (Reducing Risk in Heart Disease, 2012)…”
Section: Fish Oilsmentioning
confidence: 99%